Budżetowanie kosztów procesów logistycznych - Piechota, Robert (Cost Budgeting of Logistic Processes, 2005)
The elaboration of suitable budget of logistic cost processes depends on dismemberment of logistics area to suitable centres of responsibility. Cost accounting, which is projected for the budgeting of logistics costs should give possibility of registration of process' flow of materials and information. The elaboration of responsibility centres in logistic area is aimed to make cost centres which logistic costs can be planned.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 335-341